Effects of Language Status on Assessment and Educational Development of Basotho Learners from Minority Languages’ Backgrounds - Kolobe, Maboleba Agnes; Matsoso, Lifelile (Universitas Negeri Makassar, 2020)
This paper provides a critical overview of the theoretical and practical questions that prevail in the teaching, learning, and assessment of learners from diverse linguistic backgrounds in Lesotho. It investigates how far exclusion of minority languages affects both assessment and/or educational development of learners whose mother tongue is not Sesotho but other minority languages spoken in Lesotho. The paper advances a research-evidenced argument that the poor performance of students from such backgrounds is indicative of marginalisation and discrimination of such learners due to their language background. A constructivist qualitative study was adopted through use of focus group discussions with 246 learners and 142 teachers in 23 schools located in Botha Bothe, Mohale’s Hoek, Qacha’s Nek and Quthing districts in Lesotho. These places were selected based on their predominance of minority languages. The findings revealed diminutive if not absolute non-recognition of minority languages in teaching, learning, and assessment of learners from this linguistic background. Therefore, the study concludes that linguistically discriminative curriculum, teaching and learning and assessment educational practices can reasonably be associated with poor performance of learners. Based on these findings, the paper recommends that Lesotho’s education system should respect and embrace existence of national minority languages. Again, the curriculum, its implementation and more importantly assessment should not be divorced from linguistic background of learners.